Infectious disease diagnostic device using rapid and efficient qPCR assays on a multi-target chip: idream-qPCR - Shrestha, Kiran; Kim, Seongryeong; Han, Jiyeon; Zhang, Meng; Parajuli, Sajjan; Cho, Gyoujin (Microsystems & nanoengineering, 2025)
Photothermal conversion-based quantitative polymerase chain reaction (qPCR) is a fast, sensitive, and accurate method to diagnose infectious diseases. However, they have bottlenecks in test throughput scalability, cumbersome oil cover, and a lack of multi-target capability. Here, the authors present an infectious disease diagnostic device with rapid photothermal conversion-based efficient reverse transcription (RT)-qPCR assays on a multi-target chip (idream-qPCR). The authors innovate an off-axis mirror-based three-channel fluorescence intensity measurement method, enabling concurrent non-contact temperature control of 16 mini-well reaction chambers for qPCRs without the necessity of actuating parts. A transparent adhesive film on a graphite mixed polydimethylsiloxane (PDMS)-based PCR chip with mini-wells avoids contamination and bubbles to achieve 16 RT-qPCRs (40 photothermal cycles) within 17 min. Finally, idream-qPCR is validated by amplifying severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) N1 72 bp, RdRP 100 bp, and E 113 bp genes using Fluorescein amidites (FAM), Carboxytetramethylrhodamine (TAMRA), and Cyanine5 (CY5) fluorescent dyes, respectively, with 102.5% efficiency and a limit-of-detection (LoD) equivalent to 0.85 copies/µL. idream-qPCR can be efficiently used to prevent the spread of infectious diseases.